Monetary and fiscal policy for an economic growth with equality - Harberger, Arnold C. (1995)
There is not serious conflict, in principle, between economic growth and equality. The paper arrives to this conclusion after addressing topics like the effects of inflation on growth and economic efficiency, the key features of "good" economic policy, tax policy in developing countries, expenditure side policies designed to achieve greater equality, as well as other issues on poverty; and socio-economic mobility. On this vein, even though governments cannot significantly modify the income distribution of their societies, it is shown that the policies with a greater potential to shift society's Lorenz curve are those of the expenditure side rather than those of tire tax side.